2019
DOI: 10.3986/ac.v48i1.6738
|View full text |Cite
|
Sign up to set email alerts
|

Main hydrological features and recharge analysis of the Caposele Spring catchment, southern Italy

Abstract: UDC 556.33(450.7) Francesco Fiorillo, Libera Esposito, Mauro Pagnozzi, Zoran Stevanović & Gerardo Ventafridda: Main hydrological features and recharge analysis of the Caposele Spring catchment, southern ItalyThe Caposele spring supplies with water the Puglia region (southern Italy) since the beginning of the twentieth century by a wide and long (about 400 km) gravity-aqueduct system. Systematic spring discharge measurements exist since 1920. The annual mean discharge of spring is about 4 m 3 /sec, the spring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The α coefficient for the 19 December 2016-6 February 2017 period refers to the first recession interval recorded after the 30 October 2016 Norcia mainshock. It can be observed that the average value of the Maillet depletion coefficient α before the Norcia 2016 seismic sequence was 6.35 × 10 −3 day −1 (standard deviation = 1.31 × 10 −3 day −1 ) and, unlike in other Apennine springs [52,53], the α values were similar even for highly different initial discharge (Q 0 ). On the contrary, since the first depletion period recorded after the 30 October 2016 Norcia earthquake, the α coefficient significantly increased, with an average value of 1.34 × 10 −2 day −1 (standard deviation = 2.11 × 10 −3 day −1 ), as it can be observed in Figure 5.…”
Section: Depletion Coefficientsmentioning
confidence: 90%
“…The α coefficient for the 19 December 2016-6 February 2017 period refers to the first recession interval recorded after the 30 October 2016 Norcia mainshock. It can be observed that the average value of the Maillet depletion coefficient α before the Norcia 2016 seismic sequence was 6.35 × 10 −3 day −1 (standard deviation = 1.31 × 10 −3 day −1 ) and, unlike in other Apennine springs [52,53], the α values were similar even for highly different initial discharge (Q 0 ). On the contrary, since the first depletion period recorded after the 30 October 2016 Norcia earthquake, the α coefficient significantly increased, with an average value of 1.34 × 10 −2 day −1 (standard deviation = 2.11 × 10 −3 day −1 ), as it can be observed in Figure 5.…”
Section: Depletion Coefficientsmentioning
confidence: 90%
“…Mountain springs are one of the most strategic water resources in some parts of Italy [3][4][5]. In a typical high mountain environment, aquifers feed springs along the slopes [6].…”
Section: Introductionmentioning
confidence: 99%